BAGAIMANA MENGEVALUASI PROSES PEMBELAJARAN DI KELAS ? : SEBUAH MODEL EVALUASI ALTERNATIF - Fatik Rahayu; ayu ekasari (Media Riset Bisnis & Manajemen, 2012)
The growth of higher education institutions is increasing in an environment that is fiercely competitive one, especially in this 'globalization era'. There are not only local competitors that have to be faced, but Mere are also some global competitors. On the other side, educational literatures suggest that there is mounting pressure from customers of higher education, which include students, parents, alumni, employers and legislators to close the gap between their expectation of institutional performance and the actual performance. In this competitive environment, quality is one of the competitive priorities. Therefore, it is imperative that higher educations actively monitor the quality of their services. Understanding of stakeholders' expectation of higher education learning process is important.This paper aims to identified the stakeholders' expectation of learning process and based on this expectation we developed an instrument to evaluate learning process in class. A Focus Group Discussion of higher education stakeholders with student, instructor and user as partisipant were undertaken.Keywords: Stakeholders of higher education, Evaluation of learning process, instrument